2005
DOI: 10.1097/01.rli.0000178432.22377.6c
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Determination of Ultrasmall Particles of Iron Oxide for the Delineation of Microvasculature in the Wistar Rat Brain

Abstract: Purpose-This investigation sought to optimize ultrasmall particles of iron oxide (USPIO) contrast agent dosage for visualizing cerebral microvasculature on an 8.0-Tesla ultra high field magnetic resonance imaging system. Materials and Methods-USPIO contrast agent was intravenously administered to 3 groups of 4 rats at 1, 2, and 3 mg Fe/kg. Each animal was scanned before and after injection of USPIO using a high resolution T2*-weighted gradient recalled echo sequence with an in-plane resolution of 78 µm. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…As previously reported, microvascularity within high grade gliomas can be visualized directly on HR GRE UHF MRI 5,6,9,25. In the present study we have demonstrated that the use of USPIO as a blood pool agent enhanced the visualization of microvessels in the F98 glioma using HR GRE UHF MRI.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As previously reported, microvascularity within high grade gliomas can be visualized directly on HR GRE UHF MRI 5,6,9,25. In the present study we have demonstrated that the use of USPIO as a blood pool agent enhanced the visualization of microvessels in the F98 glioma using HR GRE UHF MRI.…”
Section: Discussionsupporting
confidence: 81%
“…A second set of GRE images were acquired approximately 30 to 60 seconds after infusion of USPIO (2 mg Fe/kg) (SHU 555 C, Supravist, Bayer Healthcare AG, Berlin) administration. The USPIO dose previously had been optimized for the imaging parameters used in this study 9. The SHU 555 C solution was diluted with 0.9% sodium chloride to 0.1 mmol/mL at room temperature before injection.…”
Section: Methodsmentioning
confidence: 99%
“…Very little leakage of contrast agent should not significantly affect MVD measurements in the recovery region or normal tissue where MVD is relatively large, but will lead to large errors in the ischemic core where MVD is very small. A higher dose of contrast agent will decrease the signal-to-noise ratio, resulting in some loss of vessel and tissue detail, and most likely this would reduce image quality even further (Laghi et al , 2004; Yang et al , 2005). Other factors affecting measurement of low MVD in the ischemic core may involve the relatively low signal-to-noise ratio of Δ R 2 and ΔR2 (3.8%; Laghi et al , 2004; Yang et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…9,18 The most important limitation of this study is that two different ferumoxytol doses were applied. In 14 out of our 19 participants ferumoxytol was injected at a constant dose of 510 mg (approximately 7 mg/kg in case of a 70-kg patient), while in five patients it was given at a dose of 4 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…8 Iron oxide nanoparticles increase the visibility of both normal and tumor microvessels in the brain on T 2 *-weighted scans. 9,10 On the other hand, for the evaluation of intracellularly trapped USPIOs in patients with central nervous system (CNS) malignancies, the 24-hour T 1 -weighted spin echo (SE) and T 2 -weighted images were found to be the most helpful. 11 …”
Section: Introductionmentioning
confidence: 99%